2012
DOI: 10.1007/s00280-012-1826-x
|View full text |Cite
|
Sign up to set email alerts
|

Metronomic oral combination chemotherapy with capecitabine and cyclophosphamide: a phase II study in patients with HER2-negative metastatic breast cancer

Abstract: Oral XC is an effective first- or second-line therapy for MBC, demonstrating high activity in both luminal A and triple-negative disease with few severe side effects. This metronomic oral combination chemotherapy could be beneficial for the treatment of HER2-negative MBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 24 publications
1
26
0
1
Order By: Relevance
“…In summary, a total of 818 patients received MCT, 383 patients received MCT combined with other therapies, and 159 patients could not be grouped (see detailed MCT schedules and registration numbers in S1 Table). It should be noted that data about tumor response from 5 studies were omitted due to the lack of adherence to the RECIST criteria [3,7,25,28,34], so were AEs data for lacking adherence to the NCICTC guidelines [18,28,3539]. The 2 trials in which patients were divided into two separate groups (MCT vs. MCT in combination with other therapy) did not present data separately for each individual group and therefore data from those studies were excluded from the subgroup analysis [25,28].…”
Section: Resultsmentioning
confidence: 99%
“…In summary, a total of 818 patients received MCT, 383 patients received MCT combined with other therapies, and 159 patients could not be grouped (see detailed MCT schedules and registration numbers in S1 Table). It should be noted that data about tumor response from 5 studies were omitted due to the lack of adherence to the RECIST criteria [3,7,25,28,34], so were AEs data for lacking adherence to the NCICTC guidelines [18,28,3539]. The 2 trials in which patients were divided into two separate groups (MCT vs. MCT in combination with other therapy) did not present data separately for each individual group and therefore data from those studies were excluded from the subgroup analysis [25,28].…”
Section: Resultsmentioning
confidence: 99%
“…[9] The various drugs used with substantial clinical effects are oral cyclophosphamide, capecetabine, methotrexate, etoposide, vinorelbine etc. [1011121314] This strategy has some definite advantages over conventional pulsed course chemotherapy like its lesser toxicity profile, better compliance and suitability for patients otherwise not fit for full dose chemotherapy. Metronomic oral cyclophosphamide (Cy) has been extensively studied and widely used for various advanced and metastatic solid tumors with variable results.…”
Section: Discussionmentioning
confidence: 99%
“…It is used singly or in combination with various chemotherapeutic and targeted agents for diverse malignancies like metastatic renal cell carcinoma, multiple myeloma, breast, prostate, head and neck and GI malignancies. [10111213] The heterogenecity of chemotherapy combinations used in above studies has made it difficult to objectively evaluate the additional value of the metronomic administration of cyclophosphamide. The combination of cyclophosphamide with celecoxib for heavily pretreated gastrointestinal tumors is found to be feasible, well tolerated and associated with a promising antitumor activity both demonstrated by pharmacodynamic markers and clinical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of these regimens is to achieve longer survival with fewer side effects. For HER2 negative breast cancers, Yoshimoto et al [60] found that TNBC patients had an overall response rate of 44.4% with a progression-free survival of 10.7 months; and for ER/PR-positive patients, the response rates were 46.4% and 12.2 months PFS. It has been postulated that this treatment modality induces endothelial cells apoptosis, resulting in angiogenesis impairment [60].…”
Section: Metastatic Diseasementioning
confidence: 99%
“…For HER2 negative breast cancers, Yoshimoto et al [60] found that TNBC patients had an overall response rate of 44.4% with a progression-free survival of 10.7 months; and for ER/PR-positive patients, the response rates were 46.4% and 12.2 months PFS. It has been postulated that this treatment modality induces endothelial cells apoptosis, resulting in angiogenesis impairment [60]. This is an interesting approach that merits further investigation considering the lack of durability in the patient response to chemotherapy seen in TNBC.…”
Section: Metastatic Diseasementioning
confidence: 99%